Порушення адаптації студентів до навчальної діяльності у вищому навчальному закладі - Глазков, Е.О. (Таврический медико-биологический вестник, 2012)
В статье поданы результаты исследования уровня тревожности (ситуативная, личностная) в
процессе обучения у студентов с использованием стандартной методики Ч.Д. Спилбергера, а также
дана оценка адаптационных возможностей личности по многоуровневому личностному опроснику
«Адаптивность» (МЛО-АМ). Дана сравнительная характеристика составляющих процесса адаптации
студентов. Определена необходимость исследования проблемы адаптации и коррекции дезадаптации
в процессе обучения. In the article the results of research of level of anxiety (situation, personality) are given in the process
of teaching for students with the use of standard method of Spilbergera Ch.D., and also the estimation of
adaptation possibilities of personality is given on a multilevel personality questionnaire «Adaptiveness» (MLOAM).
Comparative description of constituents of process of adaptation of students is given. The necessity of
research of problem of adaptation and correction of disadaptation is certain in the process of teaching.